PENGARUH MANAJEMEN PENGASUHAN TERHADAP KARAKTER SANTRI DI PONDOK PESANTREN IBNU SINA KABUPATEN BOGOR - Jakiah Darojah, Kikih; Nugraha, Acep; Hasanah, Tita (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
The purpose of this study was to determine the parenting patterns and characters of students at the Ibnu Sina Islamic Boarding School in Bogor Regency. This study used a survey method with a quantitative descriptive approach. The techniques used to process the data were descriptive statistical analysis and inferential analysis which included determinant analysis, regression, and correlation. Of the 239 children in the population, 150 students became the subjects of the study. The results showed that: 1) The performance of the parenting management of the Ibnu Sina Islamic Boarding School was assessed as very good with a relative frequency score of 78.6%. 2) The percentage of students' characters assessed varied, namely 81.6% which was included in the very good category. 3) The R Square value was 0.093 or around 9.3% which indicated that parenting patterns had a positive effect on students' characters, while the remaining 90.7% was determined by other factors.